(untitled) (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The purpose of this work is to develop and validate an appropriate solvent solution and quantitative thin layer chromatography (TLC) method for determining the aflatoxins content of chicken feeds and dietary grains. Materials and Methods: To obtain the optimal mobile phase, samples were extracted with methanol/water (3:1) + 5% sodium chloride and partitioned using several solvent systems using preparative TLC. Camag TLC scanner 3 was used to scan the TLC plates at 366 nm and quantify them using JustTLC software. The method was tested for linearity, specificity, accuracy, precision, sensitivity, and robustness in accordance with ICH recommendations, and then utilized to screen 132 Nigerian poultry/food samples for total aflatoxins (TAFs). Results: The best separation of aflatoxins was achieved using acetonitrile and dichloromethane (3:17) mobile phase over an average run time of 45 min, resulting in linear calibration curves (R2 > 0.99) in the concentration range limit of quantitation (LoQ) to 50 ng/spot with a limit of detection of <2.0 ng/g and a LoQ of <4.0 ng/gm for all aflatoxins in all spiked samples. When the proposed TLC method was compared to an optimized high-performance liquid chromatography method, an excellent linear regression was obtained (R2 > 95%). Seventy seven (58.33%) of the 132 samples examined were positive for aflatoxins, with mean values ranging from 3.57 ± 2.55 to 37.31 ± 34.06 ng/gm for aflatoxin B1 and 6.67 ± 0.00 to 38.02 ± 31.52 ng/gm for TAFs, respectively. Conclusions: The results demonstrate the feasibility of using the suggested TLC method in conjunction with a novel solvent solution (free of carcinogenic chloroform) for the rapid and accurate measurement of TAFs in foods/feeds. J. Adv. Vet. Anim. Res., 8(4): 656–670, December 2021 http://doi.org/10.5455/javar.2021.h558